2000
DOI: 10.1115/1.1351892
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Measurements of Three-Dimensional Scapular Kinematics: A Validation Study

Abstract: The validation of two noninvasive methods for measuring the dynamic three-dimensional kinematics of the human scapula with a magnetic tracking device is presented. One method consists of simply fixing a sensor directly to the acromion and the other consists of mounting a sensor to an adjustable plastic jig that fits over the scapular spine and acromion. The concurrent validity of both methods was assessed separately by comparison with data collected simultaneously from an invasive approach in which pins were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
490
3
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 526 publications
(522 citation statements)
references
References 40 publications
16
490
3
13
Order By: Relevance
“…The receiver positions of the scapula and humerus were previously validated using bone-fixed markers and shown to accurately represent movement of their respective segments. 11,19 However, validity data available for the scapula used smaller receivers than those of this study and therefore provide slightly different results. A fourth receiver was attached to a stylus, which was used for the digitization of landmarks described in the subsequent section.…”
Section: Methodsmentioning
confidence: 42%
“…The receiver positions of the scapula and humerus were previously validated using bone-fixed markers and shown to accurately represent movement of their respective segments. 11,19 However, validity data available for the scapula used smaller receivers than those of this study and therefore provide slightly different results. A fourth receiver was attached to a stylus, which was used for the digitization of landmarks described in the subsequent section.…”
Section: Methodsmentioning
confidence: 42%
“…A previous study by Karduna et al (2001) has shown that measurements obtained 121 from a scapula mounted device have errors smaller than 5° when compared to 122 measurements from bone-pins [Karduna et al, 2001]. A number of studies have also 123 reported intra-observer and inter-observer reliabilities of the locator; the values are in 124 the ranges of 3-5° for the intra-observer and 4-6° for the inter-observer errors [de 125 Groot, 1997, Meskers et al, 1998] .…”
mentioning
confidence: 99%
“…These surface sensor placements have been shown to closely track underlying bone motion in previous studies of shoulder motion. 12,13 The reliability and validity of the electromagnetic tracking systems have been well documented in shoulder biomechanics research. 7,8,10,12,14 Design and procedure The dominant arm was tested on subjects in their custom wheelchair.…”
Section: Instrumentationmentioning
confidence: 99%
“…12,13 The reliability and validity of the electromagnetic tracking systems have been well documented in shoulder biomechanics research. 7,8,10,12,14 Design and procedure The dominant arm was tested on subjects in their custom wheelchair. Sensors were attached to the thorax (sternum), scapula and humerus as described previously.…”
Section: Instrumentationmentioning
confidence: 99%